Effect of larval food amount on ovariole development in queens of Trigona spinipes (Hymenoptera, Apinae) - Lisboa, LCO; Serrao, J. E.; Cruz-Landim, C.; Campos, LAO (Blackwell Publishing, 2005)
Caste determination in Trigona spinipes Fabricius (Hymenoptera, Apidae, Meliponini) is trophogenic. Larvae that eat about 360 mu l of food become queens, while those who consume 36 mu l develop into workers. We studied the effect of larval nutrition on the number and length of ovarioles and on ovarian development in fifth instar larvae, white eyed, pink eyed and black-eyed pupae as well as newly emerged adults. All larvae have four ovarioles per ovary, while in queen pupae this number ranged from 8 to 15. Cyst formation, the cell death and other characteristics of ovary morphogenesis were the same regardless of the quantity of food consumed. These results are discussed in relation to caste differentiation in other bees.